Adsorption kinetics of partially ionized fatty acids at oil/water interface of their monomeric and liposomal solution - Muhamad, R.; Misran, Misni (Elsevier, 2017)
Fatty acid in the partially ionized form has an astounding ability to adsorb at oil/water interface. The mechanism for adsorption of fatty acids in this condition is expected to be diffusion controlled without the presence of the adsorption barrier. Based on the existing adsorption theory, we studied the kinetics of adsorption of fatty acid at pKa environment. It was observed that both the diffusion and the kinetic (barrier) models satisfactorily described the adsorption kinetics of fatty acid monomeric solution. This behavior thus leads to a contradiction in the interpretation of results. It was observed that the contradictions could occur in the controlling mechanism, the location of the barrier, and the origination of the existence of the barrier. Herein reports the contradiction observed in the kinetics of surfactant adsorption that is often overlooked. The higher affinity of fatty acids molecule for adsorption leads to the breakdown of liposome in solution. The liposome dissociation rate constant, k, obtained from the diffusion model is increased with the increase in the liposome concentration.